The Complex Web: Life - Force and Power in the Works of Ted Hughes: Exploring Nature and Power in Ted Hughes' Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Nature and animal world are the dominant themes in Ted Hughes‟s poetry, since nature manifests the elemental energy and the animals inherit those instinctive characteristics which impart them the power to accommodate with this. Hughes conceives that the whole of the universe is directed and regulated by the bigger energy that pervades like power circuit through it, he calls it - “elemental power circuit” (TCP, 103). He is convinced that it is the energy, very much real, that manifests in the various appearances of nature and is, in itself the driving force to its manifestation.